EFEKTIVITAS SPODOPTERA LITURA MULTIPLE NUKLEOPOLYHEDROSIS VIRUS (SlMNPV) HASIL PERBANYAKAN PADA SEL LINE UNTUK MENGENDALIKAN LARVA Spodoptera litura SKALA GREEN HOUSE DENGAN BERBAGAI WAKTU APLIKASI - Mahanani Tri Asri, ; Nur Ducha, (Matematika dan Sains, 2010)
The biological control is the best choice to control plant pest population. SlMNPV is the one kind of the biological control agent which effective to control the Spodoptera litura caterpillar. The caterpillar attacked to many kind of agrocultural crops like Ricinus comunis, soybean, cotton, and tobacco. The effectivenes SlMNPV reproduce cresult in cell line of to control the caterpillar in green house in various concentrations. This research conducted to know the effect of virus concentration ( 7,1 x 107 PIBs/ml, 7,1 x 108 PIBs/ml, and 7,1 x 109 PIBs/ml) to control the caterpillar (Spodoptera litura) death in three application times (the morning; 06.00; day :12.00 and evening: 16.00). The results of the research showed that the virus concentration of 7,1 x 108PIBs/ml PIBs/ml effective to control caterpillar population because the caterpillar death reached 80% (biological control standart) and the best time to applicate was evening.7 PIBs/ml, 7,1 x 108 PIBs/ml, and 7,1 x 109 PIBs/ml) to control the caterpillar (Spodoptera litura) death in three application times (the morning; 06.00; day :12.00 and evening: 16.00). The results of the research showed that the virus concentration of 7,1 x 108PIBs/ml PIBs/ml effective to control caterpillar population because the caterpillar death reached 80% (biological control standart) and the best time to applicate was evening.